The Oxford handbook of mobile music studies: Volume 1 - Gopinath, Sumanth; Stanyek, Jason (Oxford Oxford university press, 2014)
The Oxford Handbook of Mobile Music Studies consolidates an area of scholarly inquiry that examines how electrical technologies and their corresponding economies of scale have rendered music and sound increasingly mobile portable, fungible, and ubiquitous. At once a marketing term, a common mode of everyday-life performance, and an instigator of experimental aesthetics, "mobile music" opens up a space for studying the momentous transformations in the production, distribution, consumption, and experience of music and sound that took place from the late nineteenth to the early twenty-first centuries. The first volume of the handbook treats the devices, markets, and theories of mobile music, incorporating epistemologies and methodologies from a number of disciplines, including music studies, sound studies, mobility studies, communication studies, new media studies, performance studies, and more. The contributors draw on political economy and economic sociology, ethnography and autoethnography, musical and sonic transcription, analysis and hermeneutics, and historical and archival research as its primary methods. The book treats a significant number of devices, including the transistor radio, the portable gramophone, the Walkman, the iPod, the boom box, headphones and earbuds, and the cochlear implant. Its chapters cover a large swath of the world the US, the UK, Japan, Brazil, Germany, Turkey, Mexico, France, China, Jamaica, Iraq, the Philippines, India and a similarly broad array of musical styles and practices, from the recondite and subcultural to the mass-popular and global. The most comprehensive book of its kind, this handbook is a necessary reference for scholars in multiple fields.